IMPLEMENTASI KEBIJAKAN PEMERINTAH DAERAH TENTANG RETRIBUSI PELAYANAN PARKIR DI TEPI JALAN UMUM KABUPATEN POLEWALI MANDAR - Asnia Jaya; Muhammad Syaeba; Yusuf Daud (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2020)
This study aims to determine how the implementation of local government policies regarding parking fees on the side of public roads in Pekkabata Central Market, Polewali Mandar Regency. This research used a qualitative descriptive method, with data collection techniques through interviews and documentation. The results showed that the implementation of the local government policy regarding parking fees at the Pekkabata Central Market was not good because the supervision carried out by the Transportation Agency, especially from UPTD Parking, was still lacking, especially related to illegal collection practices carried out by illegal parking attendants. To emphasize the security of illegal parking attendants, it is necessary to have socialization by the local government related to Regional Regulation Number 2 of 2018 concerning Retribution for Parking Services on Public Roads and Special Parking Areas.